Контроль эффективности защитного действия опережающей отработки пластов десорбометрическим методом - Галемский, П.В. (Наукові праці УкрНДМІ НАН України, 2012)
Виконані експериментальні дослідження інтенсивності десорбції газу із зразків викидонебезпечного вугільного пласта. Визначені вимоги до методики вимірювань, десорбометру та розроблено спосіб контролю його герметичності за результатами вимірювань. Запропонована статистично обґрунтована методика контролю ефективності захисної дії. Experimental studies of intensity of desorption of gas from coal in order to control the degree of degassing after extraction off the protective coal seam were conducted. Requirements for the measuring technique and desorbometer determined. A method of control of desorbometer’s airtightness as a result of measurements was developed. Method of controlling the degree of degassing when developing protective seam statistically sound was proposed.